Mobile applications for open display networks : common design considerations - José, Rui (2013)
Mobile devices can be a powerful tool for interaction with public displays, but mobile applications supporting this form of interaction are not yet part of our everyday reality. There are no widely accepted abstractions, standards, or practices that may enable systematic interaction between mobile devices and public displays. We envision public displays to move away from a world of closed display networks to scenarios where mobile applications could allow people to interact with the myriad of displays they might encounter during their everyday trips. In this research, we study the key processes involved in this collaborative interaction between public shared displays and mobile applications. Based on the lessons learned from our own development and deployment of 3 applications, and also on the analysis of the interactive features described in the literature, we have identified 8 key processes that may shape this form of interaction: Discovery, Association, Presence Management, Exploration, Interface Migration, Controller, Media Upload and Media Download. The contribution of this work is the identification of these high-level processes and an elicitation of the main design considerations for display networks.